A Case of Recurrent Bacterial Meningitis Due to Retained 54-Year-Old Ureterodural Anastomosis. (August 2018) - D'Assumpcao, Carlos; Sandhu, Ahana; Heidari, Arash; Froush, Arman G.; Hillyer, Shahab; Chen, Joseph; Ragland, Alan
Ventriculoperitoneal shunts are the current treatment of choice for congenital hydrocephalus. It is rare for physicians to see patients with alternative types of shunting devices. Lumboureteral shunts, once popular from the 1940s to 1960s, decompress via the genitourinary system. Immediate complications were dehydration, electrolyte imbalances, infection, and the sacrifice of a functional kidney. Long-term complications include retrograde meningitis due to urinary tract infections. Three shunt types have been documented: polyethylene, silicone rubber, and ureterodural anastomosis. Routine imaging cannot detect a ureterodural anastomosis, and if suspected, computed tomography myelogram is needed for confirmation. This article presents the case of a man with long-standing ureterodural anastomosis that required ligation after recurrent episodes of acute meningitis secondary to urinary retention.